Gambaran X-Foto Schuller Pada Pasien Otitis Media Kronis Di Rumah Sakit Angkatan Laut Dr. Ramelan Surabaya Periode 20152016 - SALSABILA IRBAH AZHARI; SRI MULYATI (HANG TUAH MEDICAL JOURNAL, 2018)
Background: Chronic Otitis Media is an infection of the middle ear marked by discharge from the middle ear. A survey conducted in seven provinces in Indonesia in 1996 found the prevalence of chronic suppurative otitis media was 3% of the population of Indonesia. OMSK can cause complications such as mastoiditis, meningitis and epidural abscess. The presence of complicationscan be examined one with a Schuller photo. Objective: To determine how many cases of mastoiditis in patients with chronic otitis media. Methods: This research was a descriptive study. The research was held between December 2016-Januari 2017 at Dr. Ramelan naval hospital Surabaya. The samples used were chronic otitis media patients with and without complications of mastoiditis who had Schuller photo examination at Dr. Ramelan naval hospital Surabaya in 2015-2016 that met the inclusion criteria. Results: The samples consisted of 72 patients. The highest proportion of samples were in the group of 41-50 years as many as 17 samples (23,61%), 37 patients were male (51.39%) and 35 patients were female (48.61%). Complications of mastoiditis was found in 69 patients (95.83%) and kolesteatom in 5 patients (6.94%). Chronic Mastoiditis was found in 48 patients (66.67%), Acute Mastoiditis in 21 patients (29.17%) and 3 patients (4.16%) were normal. Conclusion: Chronic Mastoiditis was the most common complication in patients with chronic otitis media